The Arabism of Muhammad (PBUH), the Arabic of the Qur’an, its Universality, and the Reasons for its Descent in the Arabian Peninsula - Hussaini, Amal Suhail Abdul (International Journal of Psychosocial Rehabilitation, 2020)
The issue of Arabism and the Holy Quran is tackled mainly in this study due to many irresponsible views about this issue, especially the tone of its amplification, contradiction, and departure from theoretical and intellectual frameworks to the political and social frameworks in light of sectarian war which has no place in Qur’an, Islam, or even in Arabism. Therefore, in order to restore matters to their normal level, and in order to restore these concepts to their natural place at the intellectual and theoretical levels, away from the spirit of hostility and the spirit of contradiction that try to be manifested our public life, it is necessary, as a matter of entrust our legal mandate, to define the basic concepts of the issue of Arabism, the Qur’an, and Islam, and to recall the constant facts. One should not be deluded that Islam is a religion that belongs to the Arabs alone since this is not the case, and Islam is not directed only to Arabs, but it is to all people in every time and place since the emergence of its star in the sky of the Arabian Peninsula to the end of the world. Therefore and from this section, it is better to define Arabism as the group of historically formed cultural, social, and psychological features characterized by relative stability for the group called the Arab nation, and thus this definition will exclude any endeavor of exclusion on the basis of nationalism, or any secondary cultural view that would disassemble rather than collect the most important fabric of Islamic nations.